Effects of the methyl methacrylate addition, polymerization temperature and time on the MBG@PMMA core-shell structure and its application as addition in electrospun composite fiber bioscaffold. Issue 5 (1st March 2023) - Lin, Hsiu-Na; Peng, Tzu-Yu; Kung, Yu-Ruei; Chiou, Yuh-Jing; Chang, Wei-Min; Wu, Shan-Hua; Mine, Yuichi; Chen, Chin-Yi; Lin, Chung-Kwei
Abstract: Mesoporous bioactive glass (MBG) possesses a high specific surface area and excellent biocompatibility making it a promising biomaterial. In the present study, poly(methyl methacrylate) (PMMA) was coated on MBG to obtain a MBG@PMMA core-shell structure to further expand the potential applications of MBG. Changes in the MMA to MBG ratio, polymerization temperature and time were investigated to determine their effects on the core-shell structure. The as-prepared core-shell powders were evaluated using scanning electron microscopy, transmission electron microscopy, and Fourier-transform infrared spectroscopy to determine the optimal core-shell structure for electrospinning application. Electrospun composite fiber scaffolds prepared by adding MBG with or without an optimized PMMA shell were examined through microstructural observation, mechanical testing, Raman spectroscopy, and in vitro bioactivity evaluation. Experimental results showed that optimized MBG@PMMA core-shell powder was prepared using MMA: MBG = 3: 1, with polymerization at 70 °C for 4 h. The spherical core-shell powder exhibited a relatively smooth surface and the flake- or cotton-like shell structure was beneficial to electrospinning. Electrospun composite fiber scaffold prepared using MBG@PMMA powder exhibited superior mechanical performance and excellent biocompatibility compared to its shell-less MBG counterpart. Graphical abstract: Image 1